The Effect of Liquidity, Leverage, and Company Size on the Financial Performance of Healthcare Companies in 2020-2024 - Oktavia, Megna; Nurlaela, Siti; Chomsatu, Yuli (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This study aimed to investigate the impact of liquidity, leverage, and firm size on financial performance. The data source was secondary data obtained from the financial reports of health companies listed on the Indonesian Stock Exchange (IDX) for the period 2020-2024. The research population comprised healthcare companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The study employed purposive sampling, comprising a sample of 14 companies. Linear regression analysis was conducted using SPSS version 25 for data analysis techniques. The findings indicated that liquidity significantly influenced corporate financial performance, whereas leverage had no effect. Moreover, corporate size influenced financial performance.